PENERAPAN MODEL NUMBERED HEADS TOGETHER (NHT) DENGAN MEDIA HANDOUT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PENGANTAR EKONOMI DAN BISNIS (Penelitian Tindakan Kelas Di SMK Negeri 1 Karanganyar) - Sonny Galih Gumelar; Harini Harini; Aniek Hindrayani (Department of Economics Education, Universitas Sebelas Maret, 2016)
The purpose of this research is to improve activities and student learning outcomes of the introduction to business economics at class XI Marketing 2 of Vocational High School 1 Karanganyar in the academic year of 2015/2016 through implementation of Numbered Heads Together (NHT) model with Handout media. The type of this research was classroom action reseach. The subject of this research in student at XI Marketing 2 of Vocational High School 1 Karanganyar in the academic year of 2005/2016 with 36 Student. The procedures of this research are (a) planning, (b) action, (c) observation, and (d) reflection. Based on the research result, the learning process with the implementation of Numbered Heads Together (NHT) with Handout media can increase activities and learning outcomes of the student. It could be seen from the cycles I to II have improvement of student activities and student learning outcomes. Pre student activity cycles on the aspects of mental activities 41,67%, oral activities 45,37%, listening activities 55,56% dan writing activities 83,33%. Cycle I, on aspects of mental activities 69,44%, oral activities 75,00%, listening activities 88,89% and writing activities 77,78%. Cycle II on aspect of mental activities 83,33%, oral activities 82,41%, listening activities 91,67% dan writing activities 80,56%. Student learning outcomes are also increased at pre cycle have average value 73,08 (percentage of completeness 47,22%), cycle I becomes 77,31 (percentage of completeness 80,56%), cycle II becomes 80,95 (percentage of completeness 88,89%).